Inventory of Invasive Plant Species along the corridor of Kawah Ijen Nature Tourism Park, Banyuwangi, East Java - Hapsari, Lia; Basith, Abdul; Novitasiah, Hari Rusdwi (Graduate School, Universitas Brawijaya, 2014)
A field survey was conducted in November 2013 to inventory invasive plant species present along the corridor of Kawah Ijen Nature Tourism Park exploratively. Result showed that there were 11 plant species found abundantly along the corridor. Typical native species were dominated by Cyathea contaminans, Casuarina junghuhniana and Vaccinium varingiaefolium. Three species were determined as invasive alien species i.e. Chromolaena odorata, Acacia decurrens and Blumea lacera whereas five species were determined as native species but potential invaders i.e. Rubus moluccanus, Melastoma malabatrichum, Polygonum barbatum, Debregeasia longifolia and Pteridium aquilinum. In term of tourism particularly on nature-based destinations enable moving in and out of invasive alien species due to opening the access of some natural protected areas. The environmental impact of an alien species whether it becomes invasive at its destination depends on its biological key point, what ecological role the species may play, and on additional factors such as its tolerance of the gross features of the environment in the new range. Keywords: invasive plants, corridor, Kawah Ijen, Nature Tourism Park, Banyuwangi